Molecular Evaluation of miR-122 and miR-221 Gene Expression in Liver Fibrosisa - Mubark, Nawras Najah (Journal of Neonatal Surgery, 2025)
miRNAs play role in regulating and managing many body functions, and the disorders that result from a defect in the functioning of this genes may have multiple effects, such as metabolic disorders. Therefore, the current study attempts to investigate gene expression of miRNA 122 and 221 in liver fibrosis and evaluate their effects on the function of hepatocytes. present research is a case – control study, included blood samples collection from 88 fibrotic patients and 88 health individuals as control. After RNA extraction, gene expression of miRNA 122 and 221 evaluated by RT-qPCR. FUJI DRI-CHEM SLIDE are used to determine total concentration of liver enzymes (TSB, ALP, ALT, AST), Albumin, C- reactive protein (CRP). The results showed an increase in the concentration of TSB, ALP, ALT, AST and CRP in patients compared to controls and on the contrary, the concentration of albumin increased in healthy people compared with patients (P<0.05). The results of the gene expression analysis determined by real time PCR showed a lower mean fold change for miRNA 122 in patients (3.76 x2-∆∆CT) compared to controls (7.45 x 2-∆∆CT ) while we found a higher mean fold change for miRNA221 in patients (2.71x 2-∆∆CT) compared with healthy people, (0.04 x 2-∆∆CT) which led to the emergence of significant differences (P< 0.05). did not find a clear relationship between miRNA 122 with the tests performed to evaluate liver function, as the Pearson linear relationship was positive but very weak. In addition, gene expression for miRNA 221 was associated with a clear change in the activity of ALP, AST and Albumin (r= 0.260, 0.312 and 0.338 respectively). Gene expression of miRNA 122 and 221 significantly associated with liver fibrosis although we didn’t find clear correlation between these genes expression and liver function..